Hydrogenation catalyst as well as preparation method and application thereof

By using a modified alumina support with a surface rich in hydroxyl groups and a hydrogenation catalyst with Pd active components, the problem of fully hydrogenating the carbon-three-carbon and four-mixed fractions in the lightweight raw material cracking device is solved, and an efficient conversion of unsaturated hydrocarbons is achieved.

CN119897101APending Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202311402068.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The prior art is difficult to effectively deal with the problem of total hydrogenation of carbon-three-carbon quad-mixed fractions generated by lightweight raw material cracking devices, especially the low conversion rate for unsaturated hydrocarbons.

Method used

Modified alumina with hydroxyl-rich surface is used as the support, and Pd is supported as the main active component. The density of hydroxyl groups on the surface of the support is enhanced by surface treatment methods such as acidification, alkalization, crystallization and irradiation, thereby improving the support and catalytic activity of the metal active component.

Benefits of technology

High-efficiency full hydrogenation of unsaturated hydrocarbons in carbon-three-carbon quad-mixed fractions is achieved, and the conversion rate is improved, so that it can be used as a cracking or other raw material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004516937630000121
    Figure BDA0004516937630000121
  • Figure BDA0004516937630000131
    Figure BDA0004516937630000131
  • Figure BDA0004516937630000132
    Figure BDA0004516937630000132
Patent Text Reader

Abstract

The invention provides a hydrogenation catalyst and a preparation method and application thereof. The hydrogenation catalyst comprises a main active component, an auxiliary active component and a carrier. The isoelectric point regulating agent is added in the aluminum oxide preparation process, and at least two treatment methods of acidification or alkalization, crystallization and irradiation are combined, so that the hydroxyl group density on the surface of the formed aluminum oxide carrier can be greatly improved, and the conversion rate of the hydrogenation catalyst to unsaturated hydrocarbon is improved. The hydrogenation catalyst provided by the invention can be used for completely hydrogenating unsaturated hydrocarbons in C3 and C4 fractions generated by a lightweight raw material cracking device until the unsaturated hydrocarbons are saturated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and specifically relates to a hydrogenation catalyst and a preparation method and application thereof. Background Art

[0002] In recent years, cracking raw materials have shown a diversified development trend, especially light-weight ones have received widespread attention. At present, the raw materials used by ethylene plants at home and abroad are mainly naphtha, ethane, propane, butane, diesel, coal, etc. Compared with traditional naphtha cracking, light hydrocarbon cracking units have the advantages of short process flow, small footprint, low equipment investment, and high yield. In addition to the main product ethylene, cracking units using light raw materials produce by-products such as hydrogen, methane, carbon three, carbon four, as well as benzene and toluene. Among them, the content of unsaturated carbon three and carbon four is relatively small, mainly including propylene, propyne (MA), propadiene (PD), butadiene and butene. The cost of selecting hydrogenation after separation is relatively high, and they are usually fully hydrogenated and transported to the cracking furnace for use as cracking raw materials.

[0003] Chinese patent CN105727990A discloses a C3 selective hydrogenation catalyst and a preparation method thereof, wherein Al2O3 modified with an organic solution of a bipyridine derivative with a hydroxyl group is used as a carrier, and a mixed cationic solution of palladium and copper is used as a precursor of the active component. The surface tension and solvation effect of the impregnation solution are overcome by modifying the carrier, so that the palladium-copper has a better dispersion effect, is more conducive to the formation of a palladium-copper alloy, and has better selectivity and anti-coking performance.

[0004] Chinese patent CN114100615A discloses a C4 selective hydrogenation catalyst and its preparation method, which uses a modified attapulgite-montmorillonite composite material as a carrier and non-precious metal nickel as an active component. The nickel source can be nickel salt or basic nickel carbonate extracted from waste nickel-hydrogen batteries, and the acid-base synergistic catalysis is generated through the stepped channels formed inside the crystals of the composite carrier, so that the catalyst has good activity and selectivity.

[0005] The existing technical solutions mainly focus on hydrogenating the C3 or C4 fractions separately, or loading the C3 and C4 hydrogenation catalysts in layers in the hydrogenation reactor of the mixed stream. However, most C3 catalysts have certain requirements on the content of C4 fraction in the raw material, and most C4 catalysts also have low MAPD conversion rate in the raw material. Therefore, it is necessary to develop a full hydrogenation catalyst suitable for the mixed C3 and C4 fractions produced by the light raw material cracking unit. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention proposes a hydrogenation catalyst which can be used for the full hydrogenation of the C3-C4 mixed fraction produced by cracking of light raw materials, and the olefins and diolefins can be hydrogenated to saturation and then used as cracking or other raw materials.

[0007] One of the purposes of the present invention is to provide a hydrogenation catalyst, comprising: a carrier, and a main active component and a co-active component supported on the carrier, wherein the carrier is a modified alumina carrier with a surface rich in hydroxyl groups.

[0008] According to the present invention, in the hydrogenation catalyst:

[0009] The carrier is a modified alumina carrier obtained by adding an isoelectric point regulator to an alumina component and then subjecting the surface to a surface treatment;

[0010] The density of the hydroxyl groups on the surface of the carrier is 6 to 18 mmol / m 2 , preferably 6.5 to 15 mmol / m 2 ;

[0011] The average pore size of the carrier is 50-200 nm, and the most likely pore size is 100-350 nm; preferably, the average pore size of the carrier is 70-180 nm, and the most likely pore size is 110-300 nm;

[0012] The specific surface area of ​​the carrier is 5 to 280 m 2 / g, preferably 15 to 250 m 2 / g;

[0013] The bulk density of the carrier is 0.35 to 1.2 g / mL, preferably 0.45 to 1 g / mL.

[0014] According to the present invention, in the hydrogenation catalyst:

[0015] The main active component is Pd;

[0016] The auxiliary active component is selected from at least one of Ag, Ga, Bi, Ce, Pb, Cu, Au, Zn, Ga, In, Cu, As, rare earth metals, alkali metals, and alkaline earth metals, preferably at least one of Ag, Ga, Zn, Cu, Pb, Ce, and In;

[0017] The carrier contains aluminum oxide and other oxides, and the other oxides are selected from at least one of tungsten trioxide, vanadium pentoxide, antimony pentoxide, silicon oxide, zirconium oxide, manganese oxide, tin oxide, titanium oxide, ferrous oxide, cerium oxide, nickel oxide, iron oxide, copper oxide, zinc oxide, lanthanum oxide, gallium oxide, and indium oxide.

[0018] According to the present invention, in the hydrogenation catalyst:

[0019] Based on the total weight of the carrier as 100%, the content of the main active component is 0.05-0.5%, and the content of the auxiliary active component is 0.01-10%; preferably, based on the total weight of the carrier as 100%, the content of the main active component is 0.1-0.4%, and the content of the auxiliary active component is 0.01-5%;

[0020] Based on 100% of the total weight of the carrier, the content of aluminum oxide is 60 to 99.9%, preferably 65 to 98%.

[0021] The second object of the present invention is to provide a method for preparing the above-mentioned hydrogenation catalyst, and the main active component and the auxiliary metal component can be loaded onto the carrier by any method for preparing supported catalysts in the art, for example, the active component precursor is loaded onto the carrier by spraying and / or impregnation. Specifically, the method for preparing the hydrogenation catalyst comprises: impregnating the carrier with a metal compound solution containing a main active component precursor compound and an auxiliary metal component precursor compound, and obtaining the hydrogenation catalyst after drying and calcining.

[0022] According to the present invention, in the method for preparing the hydrogenation catalyst:

[0023] The main active component precursor compound is selected from one of palladium nitrate, palladium chloride, palladium oxide, palladium hydroxide, and sodium tetrachloropalladate, preferably at least one of palladium nitrate and palladium chloride;

[0024] The co-active component precursor compound is selected from at least one of Ag, Ga, Bi, Ce, Pb, Cu, Au, Zn, Ga, In, Cu, As, chlorides, nitrates, acetates, sulfates, and metal organic compounds of rare earth metals, alkali metals, and alkaline earth metals, and is preferably selected from at least one of chlorides and nitrates of Ag, Ga, Zn, Cu, Pb, Ce, and In;

[0025] In the metal compound solution, the concentration of the main active component precursor compound is 5 to 100 mg / mL, wherein the main active component precursor compound is calculated based on the metal contained therein;

[0026] The solvent in the metal compound solution is selected from at least one of water, hydrochloric acid, nitric acid, acetic acid, and alcohols, preferably water;

[0027] The drying can adopt the drying equipment and drying conditions commonly used in the prior art. For example, the drying conditions are: drying temperature is 40-180° C., and drying time is 2-24 hours; preferably, drying temperature is 50-170° C., and drying time is 4-20 hours;

[0028] The calcination can adopt the calcination equipment and calcination conditions commonly used in the prior art. For example, the calcination conditions are: calcination temperature of 200-600° C., calcination time of 2-10 hours; preferably, calcination temperature of 300-550° C., calcination time of 4-10 hours.

[0029] According to the present invention, the preparation of the carrier comprises the following steps:

[0030] (1) mixing components including an aluminum source, a forming agent, a pore expanding agent, an isoelectric point regulating agent, and a crosslinking agent solution to obtain a mixture;

[0031] (2) kneading the mixture obtained in step (1) into a mold, extruding and pelletizing, drying, and calcining to obtain a modified alumina precursor;

[0032] (3) Surface treatment of the modified alumina precursor obtained in step (2) to obtain the carrier.

[0033] According to the present invention, in the method for preparing the carrier:

[0034] The aluminum source is selected from at least one of boehmite, pseudo-boehmite, alumina, and aluminum hydroxide;

[0035] The molding agent is selected from at least one of starch, methyl cellulose, carboxymethyl cellulose, ethyl cellulose and hydroxyethyl cellulose;

[0036] The pore-enlarging agent is selected from at least one of sesbania powder, polyvinyl alcohol, polyethylene glycol, polyacrylamide, and polypropylene glycol;

[0037] The isoelectric point regulator is selected from at least one of oxides having an isoelectric point of less than 6.5 or greater than 8.5. Preferably, the isoelectric point regulator having an isoelectric point of less than 6.5 is selected from at least one of tungsten trioxide, vanadium pentoxide, antimony pentoxide, silicon oxide, zirconium oxide, manganese oxide, tin oxide, and titanium oxide; and / or, the isoelectric point regulator having an isoelectric point greater than 8.5 is selected from at least one of cerium oxide, nickel oxide, copper oxide, zinc oxide, lanthanum oxide, gallium oxide, and indium oxide;

[0038] The crosslinking agent in the crosslinking agent solution is selected from at least one of an inorganic acid and an organic acid, preferably at least one of nitric acid, sulfuric acid, hydrochloric acid, formic acid, acetic acid, citric acid, oxalic acid, ascorbic acid, and salicylic acid;

[0039] The solvent in the crosslinker solution is selected from at least one of water and an organic solvent, preferably at least one of water, methanol and ethanol.

[0040] According to the present invention, in the method for preparing the carrier:

[0041] Taking the total weight of the aluminum source, the forming agent, the pore expanding agent, and the isoelectric point regulating agent as 100%, the amount of the forming agent is 0.1-10%, the amount of the pore expanding agent is 0.1-10%, the amount of the isoelectric point regulating agent is 0.01-20%, and the balance is the aluminum source; preferably, taking the total weight of the aluminum source, the forming agent, the pore expanding agent, and the isoelectric point regulating agent as 100%, the amount of the forming agent is 0.5-8%, the amount of the pore expanding agent is 0.5-8%, the amount of the isoelectric point regulating agent is 0.05-15%, and the balance is the aluminum source;

[0042] Based on 100 g of the aluminum source, the amount of the crosslinking agent solution is 50 to 180 mL, preferably 70 to 160 mL;

[0043] The molar concentration of the crosslinking agent solution is 0.001 to 10 mol / L, preferably 0.01 to 6 mol / L.

[0044] According to the present invention, in the method for preparing the carrier:

[0045] The carrier can be formed by any existing forming technology in the art, such as at least one of fluidized granulation, agglomeration granulation, extrusion granulation, compression granulation or spray granulation;

[0046] The calcination conditions in step (2) are: calcination at 350-1200° C. for 1-10 h, preferably, calcination at 500-1150° C. for 2-8 h;

[0047] In step (3), the surface treatment is selected from at least two of acidification or alkalization, crystallization, and irradiation. Preferably, when the isoelectric point regulator is an oxide with an isoelectric point of less than 6.5 and acidification is used, the pH of the acidification treatment needs to be 0.1 to 2 higher than the isoelectric point value of the isoelectric point regulator, preferably 0.2 to 1 higher; and / or, when the isoelectric point regulator is an oxide with an isoelectric point greater than 8.5 and acidification is not used but alkalization is used, the pH of the alkalization treatment needs to be 0.1 to 4 higher than the isoelectric point value of the isoelectric point regulator, preferably 0.3 to 3.5 higher;

[0048] The modified alumina obtained after the surface treatment in step (3) needs to be dried. The drying conditions can adopt commonly used drying conditions as long as the modified alumina obtained is dry.

[0049] According to the present invention, in the method for preparing the carrier:

[0050] The acidification conditions are as follows: the acidifier in the acidifier solution is selected from at least one of nitric acid, sulfuric acid, hydrochloric acid, ascorbic acid, hydrogen peroxide, and potassium permanganate, the concentration of the acidifier in the acidifier solution is 0.001-5 mol / L, the acidification temperature is 30-80°C, and the acidification time is 0.5-8h; preferably, the concentration of the acidifier in the acidifier solution is 0.01-4 mol / L, the acidification temperature is 35-75°C, and the acidification time is 1-6h;

[0051] The alkalization conditions are as follows: the alkalizer in the alkalizer solution is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, potassium hydroxide, potassium bicarbonate, and potassium carbonate; the concentration of the alkalizer in the alkalizer solution is 0.005-5 mol / L, the alkalization temperature is 30-80°C, and the alkalization time is 0.5-8h; preferably, the concentration of the alkalizer in the alkalizer solution is 0.01-4 mol / L, the alkalization temperature is 35-75°C, and the alkalization time is 1-6h;

[0052] The crystallization conditions are as follows: the solvent used for crystallization is at least one of water, methanol and ethanol, the crystallization temperature is 120-250°C, and the crystallization time is 0.5-18h; preferably, the solvent used for crystallization is at least one of water and ethanol, the crystallization temperature is 150-200°C, and the crystallization time is 1-6h;

[0053] The irradiation conditions are: the irradiation source is γ-rays, the irradiation dose rate is 0.01-50 kGy / min, and the irradiation time is 0.2-12 h; preferably, the irradiation source is γ-rays, the irradiation dose rate is 0.1-25 kGy / min, and the irradiation time is 0.2-6 h.

[0054] In the present invention, the alumina carrier and its preparation can refer to Patent ZL202311114679.2, and the relevant contents disclosed in the aforementioned document are introduced into the present invention as a reference.

[0055] The third object of the present invention is to provide an application of the above-mentioned hydrogenation catalyst or the hydrogenation catalyst obtained by the above-mentioned preparation method in the full hydrogenation reaction of the C3C4 mixed fraction. The "full hydrogenation of the C3C4 mixed fraction" refers to hydrogenating the unsaturated hydrocarbons in the C3 and C4 mixture produced by the cracking unit to saturation and then transporting them to the cracking furnace as raw materials or as other raw materials.

[0056] The present invention adds an appropriate amount of isoelectric point regulator during the carrier preparation process, and then performs targeted surface treatment on the formed alumina carrier according to the added isoelectric point regulator, for example, combining at least two treatment methods of acidification or alkalization, crystallization, and irradiation, thereby achieving a significant increase in the density of hydroxyl groups on the surface of the alumina carrier, promoting the loading of metal active components on the carrier, and improving the conversion rate of the obtained catalyst to unsaturated hydrocarbons. The hydrogenation catalyst provided by the present invention can fully hydrogenate the unsaturated hydrocarbons in the C3C4 fraction produced by the light raw material cracking device to saturation, and can be used as cracking or other raw materials. DETAILED DESCRIPTION

[0057] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0058] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0059] Example 1

[0060] 1. Preparation of molding carrier

[0061] Weigh 100 g of pseudo-boehmite (specific surface area 274.9 m 2 / g, pore volume 0.92mL / g, bulk density 0.24g / mL), 5g polyethylene glycol, 6g sesbania powder, 4g silicon oxide (isoelectric point of 2.5) are put into a kneader and mixed evenly. Weigh 2g of concentrated sulfuric acid and 3g of citric acid and add them to 100mL of deionized water to prepare a mixed solution. Add the prepared solution into the kneader, knead and use a ball rolling machine to roll it into spherical particles with a diameter of 5mm. The particles are dried at 60°C for 6h, calcined at 1150°C for 6h, acidified with 100mL of hydrochloric acid solution with a pH of 3.0 at 40°C for 1h, and finally crystallized at 150°C for 2h in a 20wt% ethanol aqueous solution, dried at 120°C for 6h, and irradiated with 0.8kGy / min of γ rays for 4h to obtain an alumina carrier S1.

[0062] 2. Preparation of Selective Hydrogenation Catalyst

[0063] 0.16 g of silver nitrate and 0.68 g of zinc nitrate were weighed and added to 25 mL of palladium nitrate solution (Pd content was 10 mg / mL), diluted to 45.0 mL with deionized water, and sprayed onto 100 g of alumina carrier S1. The sprayed sample was placed in an oven and dried at 110° C. for 10 h and then calcined at 500° C. for 8 h to obtain catalyst C1, whose Pd loading was 0.25 wt%, Ag loading was 0.10 wt%, and zinc loading was 0.15 wt%.

[0064] Example 2

[0065] 1. Preparation of molding carrier

[0066] Weigh 100 g of pseudo-boehmite (specific surface area 274.9 m 2 / g, pore volume 0.92mL / g, bulk density 0.24g / mL), 2g hydroxymethyl cellulose, 3g starch, 5g tungsten trioxide (isoelectric point of 0.4) are put into a kneader and mixed evenly. Weigh 1.2g of concentrated sulfuric acid and 0.8g of concentrated nitric acid and add them to 100mL of deionized water to prepare a mixed solution. Add the prepared solution into the kneader, knead it, and use a ball rolling machine to roll it into spherical particles with a diameter of 5mm. The particles are dried at 60°C for 6h, calcined at 1000°C for 6h, and then the spherical particles are crystallized in the air at 170°C for 5h and acidified at 50°C for 1h with 100mL of sulfuric acid solution with a pH of 1. After acidification, dry it at 120°C for 6h to obtain the alumina carrier S2.

[0067] 2. Preparation of Selective Hydrogenation Catalyst

[0068] 0.76 g of copper nitrate was weighed and added to 25 mL of palladium nitrate solution (Pd content was 10 mg / mL), diluted to 45.0 mL with deionized water, and sprayed onto 100 g of alumina carrier S2. The sprayed sample was placed in an oven and dried at 110° C. for 10 h and then calcined at 500° C. for 8 h to obtain catalyst C2, whose Pd loading was 0.25 wt % and Cu loading was 0.2 wt %.

[0069] Example 3

[0070] 1. Preparation of molding carrier

[0071] Weigh 100 g of pseudo-boehmite (specific surface area 274.9 m 2 / g, pore volume 0.92mL / g, bulk density 0.24g / mL), 5g sesbania powder, 4g starch, 7g zirconium oxide (isoelectric point of 6.0), put into a kneader and mix evenly. Weigh 1.5g nitric acid and 2.5g citric acid and add them to 100mL deionized water to prepare a mixed solution. Add the prepared solution into the kneader, knead and use a ball rolling machine to roll into spherical particles with a diameter of 5mm. The particles were dried at 60°C for 6h, calcined at 950°C for 6h, and irradiated with 4kGy / min of gamma rays for 3h, and finally acidified at 50°C for 4h in 100mL acetic acid solution with a pH of 6.5 and dried at 120°C for 6h to obtain the alumina carrier S3.

[0072] 2. Preparation of Selective Hydrogenation Catalyst

[0073] 0.32 g of silver nitrate was weighed and added to 25 mL of palladium nitrate solution (Pd content was 10 mg / mL), diluted to 45.0 mL with deionized water, and sprayed onto 100 g of alumina support S3. The sprayed sample was placed in an oven and dried at 110° C. for 10 h and then calcined at 500° C. for 8 h to obtain catalyst C3, whose Pd loading was 0.25 wt % and Ag loading was 0.20 wt %.

[0074] Example 4

[0075] 1. Preparation of molding carrier

[0076] Weigh 100 g of pseudo-boehmite (specific surface area 274.9 m 2 / g, pore volume 0.92mL / g, bulk density 0.24g / mL), 3g methylcellulose, 4g polypropylene glycol, 6g copper oxide (isoelectric point of 9.3), 5g lanthanum oxide (isoelectric point of 10.0) are put into a kneader and mixed evenly. Weigh 3g acetic acid and 2g hydrochloric acid and add them to 100mL deionized water to prepare a mixed solution. Add the prepared solution to the kneader, knead and use a ball rolling machine to roll into spherical particles with a diameter of 5mm. The particles are dried at 60°C for 6h, calcined at 1050°C for 6h, irradiated with 2kGy / min of gamma rays for 5h, and crystallized at 200°C in 200mL of water for 3h, and finally alkalized at 60°C for 2h in 100mL sodium carbonate solution with a pH of 10.3 and dried at 120°C for 6h to obtain alumina carrier S4.

[0077] 2. Preparation of Selective Hydrogenation Catalyst

[0078] 0.16 g of silver nitrate and 0.37 g of gallium nitrate were weighed and added to 25 mL of palladium nitrate solution (Pd content was 10 mg / mL), diluted to 45.0 mL with deionized water, and sprayed onto 100 g of alumina carrier S4. The sprayed sample was placed in an oven and dried at 110° C. for 10 h and then calcined at 500° C. for 8 h to obtain catalyst C4, whose Pd loading was 0.25 wt%, Ag loading was 0.10 wt%, and Ga loading was 0.10 wt%.

[0079] Example 5

[0080] 1. Preparation of molding carrier

[0081] Weigh 100 g of pseudo-boehmite (specific surface area 274.9 m 2 / g, pore volume 0.92mL / g, bulk density 0.24g / mL), 4g sesbania powder, 5g polyacrylamide, 5g zinc oxide (isoelectric point is 9.0), put into a kneader and mix evenly. Weigh 5g oxalic acid and add it to 100mL deionized water to prepare a mixed solution. Add the prepared solution into the kneader, knead it and use a ball rolling machine to roll it into spherical particles with a diameter of 5mm. The particles were dried at 60°C for 6h, calcined at 700°C for 6h, irradiated with γ rays at 1kGy / min for 6h, crystallized at 160°C in nitrogen for 5h, and finally dried at 120°C for 6h to obtain alumina carrier S5.

[0082] 2. Preparation of Selective Hydrogenation Catalyst

[0083] 0.24 g of lead nitrate was weighed and added to 25 mL of palladium nitrate solution (Pd content was 10 mg / mL), diluted to 45.0 mL with deionized water, and sprayed onto 100 g of alumina carrier S5. The sprayed sample was placed in an oven and dried at 110° C. for 10 h and then calcined at 500° C. for 8 h to obtain catalyst C5 with a Pd loading of 0.25 wt% and a Pb loading of 0.15 wt%.

[0084] Example 6

[0085] 1. Preparation of molding carrier

[0086] Weigh 100 g of pseudo-boehmite (specific surface area 274.9 m 2 / g, pore volume 0.92mL / g, bulk density 0.24g / mL), 5g starch, 4g polyethylene glycol, 5g indium oxide (isoelectric point is 8.8), put into a kneader and mix evenly. Weigh 3g concentrated hydrochloric acid and add it to 100mL deionized water to prepare a mixed solution. Add the prepared solution to the kneader, knead it, and use a ball rolling machine to roll it into spherical particles with a diameter of 5mm. The particles are dried at 60°C for 6h, calcined at 900°C for 6h, and then alkalized at 60°C for 5h in 100mL potassium bicarbonate solution with a pH of 9.5, and finally irradiated with 5kGy / min of gamma rays for 3h to obtain the alumina carrier S6.

[0087] 2. Preparation of Selective Hydrogenation Catalyst

[0088] 0.40 g of cerium nitrate and 0.39 g of indium nitrate were weighed and added to 25 mL of palladium nitrate solution (Pd content was 10 mg / mL), diluted to 45.0 mL with deionized water, and sprayed onto 100 g of alumina carrier S6. The sprayed sample was placed in an oven and dried at 110° C. for 10 h and then calcined at 500° C. for 8 h to obtain catalyst C6, whose Pd loading was 0.25 wt%, Ce loading was 0.10 wt%, and In loading was 0.15 wt%.

[0089] Comparative Example 1

[0090] The carrier was prepared according to the method of Example 1, without adding an isoelectric point regulator, and without crystallization, acidification, or irradiation treatment after high-temperature calcination, to obtain carrier S7. The catalyst preparation method was the same as that of Example 1 to obtain catalyst D1.

[0091] Comparative Example 2

[0092] The carrier was prepared according to the method of Example 1, but no crystallization, acidification or irradiation treatment was performed after high temperature calcination to obtain carrier S8. The catalyst was prepared according to Example 1 to obtain catalyst D2.

[0093] Comparative Example 3

[0094] The carrier was prepared according to the method of Example 4, but no crystallization, alkalization or irradiation treatment was performed after high temperature calcination to obtain carrier S9. The catalyst was prepared according to Example 4 to obtain catalyst D3.

[0095] Comparative Example 4

[0096] The carrier was prepared according to the method of Example 1, and after high temperature calcination, no crystallization or irradiation treatment was performed to obtain carrier S10. The catalyst was prepared according to Example 1 to obtain catalyst D4.

[0097] Comparative Example 5

[0098] The carrier was prepared according to the method of Example 1, and no acidification or irradiation treatment was performed after high temperature calcination to obtain carrier S11. The catalyst was prepared according to Example 1 to obtain catalyst D5.

[0099] Comparative Example 6

[0100] The carrier was prepared according to the method of Example 4, but no crystallization or alkalization treatment was performed after high temperature calcination to obtain carrier S12. The catalyst was prepared according to Example 4 to obtain catalyst D6.

[0101] The test instruments and test conditions used in the embodiments and comparative examples are as follows:

[0102] The specific surface area was measured by nitrogen physical adsorption BET method;

[0103] The bulk density was calculated by measuring the mass of 100 mL of alumina support, and the average value was taken after measuring each sample three times;

[0104] The pore volume and the most probable pore diameter were measured by mercury intrusion method;

[0105] Surface hydroxyl group density measurement method: weigh 0.1g of the carrier, put it into a quartz tube, pre-treat it at 450℃ under argon for 0.5h, then start the in-situ hydrogen-deuterium exchange experiment, use a mass spectrometer to record the changes in hydrogen and deuterium signals, and then use the specific surface area and mass normalization to calculate the carrier surface hydroxyl group density.

[0106] The physical property test results of the alumina carrier prepared in the examples and comparative examples are shown in Table 1.

[0107] Table 1. Physical property test results of alumina carriers in Examples and Comparative Examples

[0108]

[0109] It can be seen from Table 1 that the content and density of hydroxyl groups on the surface of the alumina support prepared by the method of the present invention are significantly higher. At the same time, by adjusting the type and proportion of raw materials, isoelectric point species and corresponding surface treatment methods, the density of hydroxyl groups on the surface of the alumina support can be finely controlled.

[0110] Test Case

[0111] 20 mL of the catalyst in the above examples and comparative examples were added to an adiabatic fixed bed reactor, and the C3C4 mixed feedstock was fed into the selective hydrogenation reactor from top to bottom. The reactor inlet temperature was 45°C, the pressure was 3.0 MPa, and the liquid space velocity (LHSV) calculated based on the feed amount was 60 h -1 The composition of the raw materials is shown in Table 2, and the evaluation results are shown in Table 3.

[0112] Among them, gas chromatography is used to detect the component content of the raw material and the material after hydrogenation using various catalysts.

[0113] Unsaturated hydrocarbon conversion rate = (molar content of unsaturated hydrocarbons in the feedstock - molar content of unsaturated hydrocarbons in the product) / molar content of unsaturated hydrocarbons in the feedstock * 100%

[0114] Table 2. Raw material composition

[0115]

[0116] (MAPD is the total amount of propyne and propadiene)

[0117] Table 3 Catalyst evaluation results

[0118]

[0119] The contents of the components in the hydrogenated products in Table 3 are the weight percentages calculated after deducting the hydrogen content. The results of using the above catalyst for full hydrogenation of C3C4 mixed fractions show that the use of the catalyst of the present invention can completely react the dienes in the mixed fractions, and the conversion rate of unsaturated hydrocarbons is higher.

Claims

1. A hydrogenation catalyst comprising: A carrier, and a main active component and an auxiliary active component loaded on the carrier, wherein the carrier is a modified alumina carrier with a surface rich in hydroxyl groups.

2. The hydrogenation catalyst according to claim 1, characterized in that The carrier is a modified alumina carrier obtained by adding an isoelectric point regulator to an alumina component and then subjecting the surface to a surface treatment; and / or, The density of the hydroxyl groups on the surface of the carrier is 6 to 18 mmol / m 2 , preferably 6.5 to 15 mmol / m 2 and / or, The average pore size of the carrier is 50-200 nm, and the most probable pore size is 100-350 nm; preferably, the average pore size of the carrier is 70-180 nm, and the most probable pore size is 110-300 nm; and / or, The specific surface area of ​​the carrier is 5 to 280 m 2 / g, preferably 15 to 250 m 2 / g; and / or, The bulk density of the carrier is 0.35 to 1.2 g / mL, preferably 0.45 to 1 g / mL.

3. The hydrogenation catalyst according to claim 1, characterized in that The main active component is Pd; and / or, The auxiliary active component is selected from at least one of Ag, Ga, Bi, Ce, Pb, Cu, Au, Zn, Ga, In, Cu, As, rare earth metals, alkali metals, and alkaline earth metals, preferably at least one of Ag, Ga, Zn, Cu, Pb, Ce, and In; and / or, The carrier contains aluminum oxide and other oxides, and the other oxides are selected from at least one of tungsten trioxide, vanadium pentoxide, antimony pentoxide, silicon oxide, zirconium oxide, manganese oxide, tin oxide, titanium oxide, ferrous oxide, cerium oxide, nickel oxide, iron oxide, copper oxide, zinc oxide, lanthanum oxide, gallium oxide, and indium oxide.

4. The hydrogenation catalyst according to claim 1, characterized in that Based on the total weight of the carrier as 100%, the content of the main active component is 0.05-0.5%, and the content of the auxiliary active component is 0.01-10%; preferably, based on the total weight of the carrier as 100%, the content of the main active component is 0.1-0.4%, and the content of the auxiliary active component is 0.01-5%; and / or, Based on 100% of the total weight of the carrier, the content of aluminum oxide is 60 to 99.9%, preferably 65 to 98%.

5. A method for preparing the hydrogenation catalyst according to any one of claims 1 to 4, comprising: The carrier is impregnated with a metal compound solution containing a main active component precursor compound and an auxiliary metal component precursor compound, and after drying and calcining, the hydrogenation catalyst is obtained.

6. The preparation method according to claim 5, characterized in that: The main active component precursor compound is selected from one of palladium nitrate, palladium chloride, palladium oxide, palladium hydroxide, and sodium tetrachloropalladate, preferably at least one of palladium nitrate and palladium chloride; and / or, The co-active component precursor compound is selected from at least one of Ag, Ga, Bi, Ce, Pb, Cu, Au, Zn, Ga, In, Cu, As, chlorides, nitrates, acetates, sulfates, and metal organic compounds of rare earth metals, alkali metals, and alkaline earth metals, preferably at least one of chlorides and nitrates of Ag, Ga, Zn, Cu, Pb, Ce, and In; and / or, In the metal compound solution, the concentration of the main active component precursor compound is 5 to 100 mg / mL, wherein the main active component precursor compound is calculated based on the metal contained in it; and / or, The solvent in the metal compound solution is selected from at least one of water, hydrochloric acid, nitric acid, acetic acid and alcohols, preferably water; and / or, The drying conditions are: drying temperature of 40-180°C, drying time of 2-24h; preferably, drying temperature of 50-170°C, drying time of 4-20h; and / or, The calcination conditions are: calcination temperature is 200-600° C., and calcination time is 2-10 hours; preferably, calcination temperature is 300-550° C., and calcination time is 4-10 hours.

7. The preparation method according to claim 5, characterized in that: The preparation of the carrier comprises the following steps: (1) mixing components including an aluminum source, a forming agent, a pore expanding agent, an isoelectric point regulating agent, and a crosslinking agent solution to obtain a mixture; (2) kneading the mixture obtained in step (1) into a mold, extruding and pelletizing, drying, and calcining to obtain a modified alumina precursor; (3) Surface treatment of the modified alumina precursor obtained in step (2) to obtain the carrier.

8. The preparation method according to claim 7, characterized in that: The aluminum source is selected from at least one of boehmite, pseudo-boehmite, alumina, and aluminum hydroxide; and / or, The molding agent is selected from at least one of starch, methyl cellulose, carboxymethyl cellulose, ethyl cellulose and hydroxyethyl cellulose; and / or, The pore-enlarging agent is selected from at least one of sesbania powder, polyvinyl alcohol, polyethylene glycol, polyacrylamide and polypropylene glycol; and / or, The isoelectric point regulator is selected from at least one of oxides having an isoelectric point of less than 6.5 or greater than 8.

5. Preferably, the isoelectric point regulator having an isoelectric point of less than 6.5 is selected from at least one of tungsten trioxide, vanadium pentoxide, antimony pentoxide, silicon oxide, zirconium oxide, manganese oxide, tin oxide, and titanium oxide; and / or, the isoelectric point regulator having an isoelectric point greater than 8.5 is selected from at least one of cerium oxide, nickel oxide, copper oxide, zinc oxide, lanthanum oxide, gallium oxide, and indium oxide; and / or, The crosslinking agent in the crosslinking agent solution is selected from at least one of an inorganic acid and an organic acid, preferably at least one of nitric acid, sulfuric acid, hydrochloric acid, formic acid, acetic acid, citric acid, oxalic acid, ascorbic acid and salicylic acid; and / or, The solvent in the crosslinker solution is selected from at least one of water and an organic solvent, preferably at least one of water, methanol and ethanol.

9. The preparation method according to claim 7, characterized in that: Based on the total weight of the aluminum source, the forming agent, the pore expanding agent, and the isoelectric point regulating agent as 100%, the amount of the forming agent is 0.1-10%, the amount of the pore expanding agent is 0.1-10%, and the amount of the isoelectric point regulating agent is 0.01-20%; preferably, based on the total weight of the aluminum source, the forming agent, the pore expanding agent, and the isoelectric point regulating agent as 100%, the amount of the forming agent is 0.5-8%, the amount of the pore expanding agent is 0.5-8%, and the amount of the isoelectric point regulating agent is 0.05-15%; and / or, Based on 100 g of the aluminum source, the amount of the crosslinking agent solution is 50 to 180 mL, preferably 70 to 160 mL; and / or, The molar concentration of the crosslinking agent solution is 0.001 to 10 mol / L, preferably 0.01 to 6 mol / L.

10. The preparation method according to claim 7, characterized in that: The calcination conditions in step (2) are: calcination at 350-1200° C. for 1-10 h, preferably, calcination at 500-1150° C. for 2-8 h; and / or, In step (3), the surface treatment is selected from at least two of acidification or alkalization, crystallization, and irradiation. Preferably, when the isoelectric point regulator is an oxide with an isoelectric point of less than 6.5 and acidification is used, the pH of the acidification treatment needs to be 0.1 to 2 higher than the isoelectric point value of the isoelectric point regulator, preferably 0.2 to 1 higher; and / or, when the isoelectric point regulator is an oxide with an isoelectric point greater than 8.5 and acidification is not used and alkalization is used, the pH of the alkalization treatment needs to be 0.1 to 4 higher than the isoelectric point value of the isoelectric point regulator, preferably 0.3 to 3.5 higher; and / or, The modified alumina obtained after the surface treatment in step (3) needs to be dried.

11. The preparation method according to claim 10, characterized in that: The acidification conditions are: the acidifier in the acidifier solution is selected from at least one of nitric acid, sulfuric acid, hydrochloric acid, acetic acid, ascorbic acid, hydrogen peroxide, and potassium permanganate, and / or the concentration of the acidifier in the acidifier solution is 0.001-5 mol / L, and / or the acidification temperature is 30-80°C, and / or the acidification time is 0.5-8h; preferably, the concentration of the acidifier in the acidifier solution is 0.01-4 mol / L, and / or the acidification temperature is 35-75°C, and / or the acidification time is 1-6h; and / or, The alkalization conditions are: the alkalizer in the alkalizer solution is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, potassium hydroxide, potassium bicarbonate, and potassium carbonate, and / or the concentration of the alkalizer in the alkalizer solution is 0.005-5 mol / L, and / or the alkalization temperature is 30-80°C, and / or the alkalization time is 0.5-8h; preferably, the concentration of the alkalizer in the alkalizer solution is 0.01-4 mol / L, and / or the alkalization temperature is 35-75°C, and / or the alkalization time is 1-6h; and / or, The crystallization conditions are: the solvent used for crystallization is at least one of water, methanol, and ethanol, and / or the crystallization temperature is 120-250° C., and / or the crystallization time is 0.5-18 hours; preferably, the solvent used for crystallization is at least one of water and ethanol, and / or the crystallization temperature is 150-200° C., and / or the crystallization time is 1-6 hours; and / or, The irradiation conditions are: the irradiation source is γ rays, and / or the irradiation dose rate is 0.01 to 50 kGy / min, and / or the irradiation time is 0.2 to 12 h; preferably, the irradiation source is γ rays, and / or the irradiation dose rate is 0.1 to 25 kGy / min, and / or the irradiation time is 0.2 to 6 h.

12. Use of the hydrogenation catalyst according to any one of claims 1 to 4 or the hydrogenation catalyst obtained by the preparation method according to any one of claims 5 to 11 in the full hydrogenation reaction of a C3-C4 mixed fraction.

Citation Information

Patent Citations

  • Preparation method of Pd-Cu-series supported hydrogenation catalyst

    CN105727990A

  • C4 fraction selective hydrogenation catalyst and preparation method thereof

    CN114100615A

  • Modified aluminum oxide with high hydroxyl density surface as well as preparation method and application of modified aluminum oxide

    CN119551697A

  • Hydrogenation catalyst, preparation method and uses thereof

    CN101433853A

  • Hydrogenation method for unsaturated hydrocarbon in hydrocarbon stream

    CN102250638A